2016
DOI: 10.1128/jvi.00863-16
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Regulators Are Important for Ecotropic Murine Leukemia Virus Infection

Abstract: During the early steps of infection, retroviruses must direct the movement of the viral genome into the nucleus to complete their replication cycle. This process is mediated by cellular proteins that interact first with the reverse transcription complex and later with the preintegration complex (PIC), allowing it to reach and enter the nucleus. For simple retroviruses, such as murine leukemia virus (MLV), the identities of the cellular proteins involved in trafficking of the PIC in infection are unknown. To id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
1
25
1
Order By: Relevance
“…Several screens have revealed that cytoskeleton-associated proteins are important in different stages of retrovirus replication (8,17). Following that line, we identified dynein and its regulators as important parts of the host cell machinery required for MLV infection (16), with the dynein regulators seeming to be essential for a step before nuclear entry but after reverse transcription. We also reported that the dynein intermediate chain is important for MLV infection, since its knockdown significantly reduced MLV infection.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Several screens have revealed that cytoskeleton-associated proteins are important in different stages of retrovirus replication (8,17). Following that line, we identified dynein and its regulators as important parts of the host cell machinery required for MLV infection (16), with the dynein regulators seeming to be essential for a step before nuclear entry but after reverse transcription. We also reported that the dynein intermediate chain is important for MLV infection, since its knockdown significantly reduced MLV infection.…”
mentioning
confidence: 73%
“…We recently demonstrated that the MLV preintegration complex (PIC) associates with dynein and dynein regulators (16); specifically, the dynein intermediate chain DYNC1I2 is required for MLV infection. The dynein intermediate chain is not only important for cargo binding but also essential for the association of dynein light chains with the complex (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations